2007
DOI: 10.1007/s00531-007-0225-8
|View full text |Cite
|
Sign up to set email alerts
|

Syn-collisional transform faulting of the Tan-Lu fault zone, East China

Abstract: Origin of the continental-scale Tan-Lu fault zone (TLFZ), East China, remains controversial. About 550 km sinistral offset of the Dabie orogenic belt (DOB) and Sulu orogenic belt (SOB) is shown along the NE-NNEstriking TLFZ. Syn-collisional, sinistral ductile shear belts in the TLFZ have been identified. Thirteen phengite bulk separates from the mylonites were dated by the 40 Ar/ 39 Ar method. They gave cooling ages of the 198-181 Ma for the shear belts along the eastern margin of the DOB and 221-210 Ma from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
104
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(112 citation statements)
references
References 46 publications
3
104
1
4
Order By: Relevance
“…The TLFZ experienced obvious sinistral motion during the Mesozoic (Xu et al, 1987;Xu and Zhu, 1994;Gilder et al, 1999;Zhu et al, 2005;G. Zhu et al, 2009;Zhu et al, 2012), whereas it experienced dextral motion during the Cenozoic (Allen et al, 1997;Hsiao et al, 2004;Gong et al, 2010;Huang et al, 2012a,b).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The TLFZ experienced obvious sinistral motion during the Mesozoic (Xu et al, 1987;Xu and Zhu, 1994;Gilder et al, 1999;Zhu et al, 2005;G. Zhu et al, 2009;Zhu et al, 2012), whereas it experienced dextral motion during the Cenozoic (Allen et al, 1997;Hsiao et al, 2004;Gong et al, 2010;Huang et al, 2012a,b).…”
Section: Introductionmentioning
confidence: 94%
“…Zhu et al, 2009;Zhu et al, 2012), whereas it experienced dextral motion during the Cenozoic (Allen et al, 1997;Hsiao et al, 2004;Gong et al, 2010;Huang et al, 2012a,b). Compared with the history of Mesozoic sinistral motion constrained by geochronological data (Yin and Nie, 1993;Zhu et al, 2005;G. Zhu et al, 2009;Zhu et al, 2012), the history of dextral motion during the Cenozoic has not been constrained by any Gondwana Research xxx (2014) xxx-xxx methods and therefore, a significant unresolved question is when did the dextral motion occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collision along the Mianlue ocean began at its east, causing deep subduction of the Dabie-Sulu orogen, formation of the HP/UHP rocks, and their later rapid exhumation by thrust [54]. Zhu et al [77] also concluded that the Tanlu fault, located between the Dabie-Sulu orogen, underwent a northwest-vergent, strike-slipping subduction and collision in the Late Triassic.…”
Section: Analysis Of Geodynamicsmentioning
confidence: 99%
“…In addition to the active tectonics taking place in the interior of Chinese mainland, forces from outside have exerted influence to the evolution of Chinese mainland, resulting in tectonic activities along major faults. The R. Gao (&) Institute of Geology, Chinese Academy of Geological Sciences, Beijing 100024, China e-mail: ruigao126@126.com most famous example is the Tanlu fault zone, which was initiated during Indosinian orogeny (Xu et al 1987;Zhu et al 2009) but was reactivated during Cenozoic with a reorganization of the plate tectonics (Chen et al 2006).…”
mentioning
confidence: 99%